Pengaruh Communal Activation untuk Membentuk Brand Loyalty Produk Minuman - Prabowo, Hartiwi; Muchardie, Brian Garda; Handrimurtjahjo, Dedy (Bina Nusantara University, 2012)
Established in 1974, PT Sinar Sosro is the first ready-to-drink tea beverage in bottles in Indonesia and in the world. Teh Botol Sosro market position is the leader in ready to drink tea industry. One of the leading products of PT Sinar Sosro is Teh Botol Sosro glass bottle often called RGB (returnable Glass Bottle). To meet the loversâ needs anywhere they are, the latest innovation from Teh Botol Sosro products is Teh Botol Sosro Less Sugar which was launched on August 20, 2008. As the time passes by, the market condition encourages a change in marketing plan that leads to a decentralized system (horizontal) in which the customer demands the same service from the same brand from any location they are. This era is called the New Wave Marketing (2008), which is still running today. The purpose of this research is to analyze the influence of communal activation of the buying decisions to increase brand loyalty in Teh Botol Sosro Less Sugar product. Data collecting technique is the questionnaire to members of the online community Botol Sosro Less Sugar and interviews, while the data analysis technique using path analysis. Path Analysis Results show there was an impact dan significant between Communal Activation and Buying Decisions, and there was also a positive correlation and significant between Buying Decisions and Brand Loyalty.